Comment on “Preserved Feedforward But Impaired Top-Down Processes in the Vegetative State” - King, Jean-Rémi (Science, 2011)
Boly et al. (Reports, 13 May 2011, p. 858) investigated cortical connectivity patterns in patients suffering from a disorder of consciousness, using electroencephalography in an auditory oddball paradigm. We point to several inconsistencies in their data, including a failure to replicate the classical mismatch negativity. Data quality, source reconstruction, and statistics would need to be improved to support their conclusions.